An electrode material suitable for large current and its application

By combining nanocellulose gel and thin-layer graphene nanosheets with micro-scale copper powder to form a composite material and annealing at high temperature, the problem of poor durability of pure copper electrode materials during long-term use of large currents is solved, and higher conductivity and mechanical strength are achieved, and the service life of the equipment is extended.

CN119753420APending Publication Date: 2025-04-04NINGBO YONGKE ACOUSTIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967153.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing pure copper electrode materials have poor durability in long-term use of large currents, which are prone to wear and deformation of the contact surface due to thermal expansion and accumulation of thermal stress, affecting the conductivity and equipment safety.

Method used

A composite material of micro-scale copper powder, nanocellulose gel and thin-layer graphene nanosheets is used to uniformly distribute graphene through gel assistance to form a continuous conductive network, and annealing at high temperatures to enhance the conductive and mechanical properties of the material.

Benefits of technology

It improves the conductivity and mechanical strength of the electrode material, extends the service life of the equipment, reduces production costs, and effectively prevents poor electrode contact and overheating problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753420A_ABST
    Figure CN119753420A_ABST
Patent Text Reader

Abstract

The present application relates to the field of electrode material technology, and in particular to an electrode material suitable for large current and its application, which includes 30-50 parts of micron-grade copper powder, 3-6 parts of nanocellulose gel, and 0.5-2 parts of thin-layer graphene nanosheets; its preparation method includes the following technical steps: mixing micron-grade copper powder with nanocellulose gel, and then mixing it with thin-layer graphene nanosheets, evaporating the water of the final mixed product under vacuum conditions, and then annealing it under high temperature conditions to obtain a to-be-treated object; then sieving the to-be-treated object to obtain a copper-based composite material. The present application uses nanocellulose gel as a binder to evenly distribute graphene particles on the surface of copper powder, and then uses high-temperature annealing to form a close interface between the two, and uses the characteristics of graphene particles to give copper powder stronger mechanical properties to improve the service life of the electrode made of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode materials, and in particular to an electrode material suitable for large currents and its application. Background Art

[0002] With the widespread development of high current applications, higher requirements are placed on the performance of electrode materials. Currently, most conventional electrode materials on the market are still made of pure copper. Although copper is an excellent conductive material and is widely used in the field of electrodes, pure copper electrode materials show obvious limitations when facing long-term high current loads, especially in terms of durability.

[0003] First, although copper has excellent conductivity, due to its low mechanical strength, electrodes made of pure copper are prone to thermal expansion and accumulation of thermal stress during long-term high current flow, which can cause wear and deformation of the electrode contact surface, thereby affecting the contact performance and conductivity of the electrode.

[0004] Secondly, due to the lack of sufficient structural reinforcement, pure copper electrodes are prone to loosening or aggregation under long-term high current loads, which will further aggravate the wear problem of the electrodes. This wear will lead to poor contact between the electrodes, increase the contact resistance, affect the efficiency of power transmission, and may even cause electrode failure. As the wear phenomenon worsens, uneven current distribution will appear on the electrode surface, causing heat to accumulate and form "hot spots", which may cause serious problems such as overheating, short circuit or equipment damage, seriously affecting the safety and stability of the equipment.

[0005] Therefore, in view of the poor durability of existing pure copper electrode materials during long-term use of high current, it is urgent to find a new electrode material solution to improve its durability and thus ensure the service life of the equipment. Summary of the invention

[0006] In order to solve the existing problems and improve the durability of copper electrode materials, the present application provides an electrode material suitable for large currents and its application.

[0007] The present application provides an electrode material suitable for large current and its application using the following technical solutions:

[0008] In the first aspect, the present application provides an electrode material suitable for large currents, using the following technical solution:

[0009] An electrode material suitable for large currents, comprising, by weight, 30-50 parts of micron-grade copper powder, 3-6 parts of nanocellulose gel, and 0.5-1.8 parts of thin-layer graphene nanosheets; a preparation method thereof comprises the following technical steps:

[0010] 1) mixing micron-sized copper powder and nanocellulose gel to obtain a first mixture;

[0011] 2) mixing the first mixture with the thin-layer graphene nanosheet to obtain a second mixture;

[0012] 3) evaporating the water from the second mixture under vacuum conditions for 1-4 hours, and then annealing the mixture at 750-850° C. to obtain a product to be processed;

[0013] 4) Screening the material to be treated to obtain a copper-based composite material.

[0014] Preferably, the nanocellulose gel is nanobamboo cellulose gel.

[0015] By adopting the above technical solutions, bamboo cellulose is low-cost, stable in a variety of chemical environments, highly reliable, and has excellent mechanical strength and elasticity, which can improve the strength of the finished electrode material; in addition, nano bamboo cellulose gel has an extremely high specific surface area, which makes it perform well in the adsorption field, and can better cooperate with the adsorption of thin-layer graphene nanosheets to further improve the strength of the finished product.

[0016] Preferably, the mass concentration of nanocellulose in the nanocellulose gel is 0.4-0.65%.

[0017] By adopting the above technical solution, a jelly-like gel can be obtained within the mass concentration range, and the gel has higher strength and stability.

[0018] Preferably, in step 4), the material to be processed is screened through a 4500-5000 mesh vibrating screen.

[0019] By adopting the above technical solution, unbound thin-layer graphene nanosheets can be screened out at this time, leaving only the required copper-based composite particles, thereby ensuring the qualified rate of the finished products subsequently made using the screened products.

[0020] In the second aspect, an application of an electrode material suitable for large current adopts the following technical solution:

[0021] An application of electrode materials suitable for large currents includes an upper electrode and a lower electrode bonded together, wherein the upper end of the lower electrode is provided with contact bridges on both sides of the upper electrode, the upper end of the upper electrode is provided with a guide column, and the outer periphery of the guide column is provided with a spring.

[0022] Preferably, the contact bridge is a multi-layer thin metal sheet structure, and a gap is left between upper and lower adjacent metal sheets.

[0023] By adopting the above technical solution, multiple layers of thin metal sheets are stacked to replace the conventional block structure, which saves the required raw materials without affecting the flow capacity.

[0024] Preferably, the contact bridge is a multi-layer thin copper sheet structure.

[0025] In summary, the present application includes at least one of the following beneficial technical effects:

[0026] 1. With the aid of gel, nano-graphene is evenly distributed on the surface of copper powder, forming a continuous and uniform graphene framework. On this basis, annealing is performed under specific high temperature conditions to avoid agglomeration between particles and maintain good loose spherical particles, ensuring a close interface between the copper matrix and nano-graphene, thereby improving the conductivity and mechanical strength of the composite material, making it more suitable for long-term application requirements in high current environments;

[0027] 2. Using low-cost bamboo cellulose and low graphene loading can achieve the purpose of close integration, effectively reduce production costs, and facilitate industrial promotion;

[0028] 3. During actual use, the contact surface between the upper electrode and the lower electrode will wear, resulting in poor contact between the upper and lower electrodes, affecting their flow capacity. When the application is assembled in the equipment, the spring will be compressed, thereby driving the upper electrode to always have a tendency to stick to the lower electrode, ensuring the long-term use of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the overall structure of the electrode material used in Example 1 of the present application.

[0030] Explanation of the reference numerals: 1. upper electrode; 2. lower electrode; 3. contact bridge; 4. guide column; 5. spring; 6. mounting hole. DETAILED DESCRIPTION

[0031] The present application is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0032] raw material

[0033] Micron-grade copper powder: spherical powder, average diameter 20 μm, purity 99.99%, purchased from Shanghai Yanbei New Material Technology Co., Ltd.

[0034] Nano bamboo cellulose gel: mass concentration 0.6%, purchased from Nanjing Tianlu Nanotechnology Co., Ltd.

[0035] Thin-layer graphene nanosheets: CAS No. 1034343-98-0, carbon content 99 at% EDS, conductivity 450-650 S / cm, water content <2 wt%, purchased from Shanghai Yanbei New Material Technology Co., Ltd.

[0036] Example

[0037] Example 1

[0038] Examples 1 and 2 use the same preparation process, but the specific component ratios are different, and the specific ratios are as follows.

[0039] Table 1 Specific raw material ratio table of Examples 1 and 2

[0040]

[0041]

[0042] Preparation process:

[0043] 1) putting the micron-sized copper powder and the nano bamboo cellulose gel into a high-speed mixer and mixing them at a speed of 3000 rpm / min for 30 minutes to obtain a first mixture;

[0044] 2) The first mixture and the thin-layer graphene nanosheets were put into a high-speed mixer and mixed at a rotation speed of 3000 rpm / min for 40 minutes to obtain a second mixture.

[0045] 3) After evaporating the water of the second mixture under vacuum conditions at 60°C for 2 hours, the mixture is transferred to a quartz tube, ammonia decomposition gas (H2+N2) is introduced, and the mixture is slowly heated to 800°C at a heating rate of 10°C / min, and the reducing protective atmosphere is maintained for 2 hours. Subsequently, a fan is used to accelerate cooling, and the temperature is rapidly reduced to room temperature at a rate of 25°C / min to obtain the object to be treated.

[0046] 4) The object to be processed is screened through a 5000-mesh vibrating screen to remove the thin layer of graphene nanosheets to obtain a copper-based composite material.

[0047] Specific applications:

[0048] The material obtained in Example 1 is made into electrodes according to application requirements. Figure 1 , an application of an electrode material suitable for large current is obtained by assembling, including an upper electrode 1 and a lower electrode 2 which are attached to each other, and the upper electrode 1 and the lower electrode 2 are fixed by bolts. A guide column 4 is integrally formed at the upper end of the upper electrode 1, and a spring 5 is sleeved on the outer periphery of the guide column 4. When the assembly is installed as a whole in a specific device, the spring 5 is subjected to pressure from above, thereby driving the upper electrode 1 to always have a tendency to approach the lower electrode 2.

[0049] A contact bridge 3 is fixed to both sides of the upper electrode at the upper end of the lower electrode 2, and the side wall of the contact bridge 3 facing the upper electrode 1 is in contact with the side wall of the upper electrode 1. The contact bridge 3 is a multi-layer thin metal sheet structure, and a gap is left between the upper and lower metal sheets. The present application takes the contact bridge 3 as an example of a multi-layer thin copper sheet structure stacked up and down. The front and rear ends of the contact bridge 3 are pressed tightly, and the front end of the contact bridge is locked to the upper end of the lower electrode by bolts. The rear end of the contact bridge is also provided with a mounting hole 6.

[0050] Comparative Example

[0051] Comparative Example 1

[0052] Comparative Example 1 uses the same raw material ratio as Example 1, but in terms of raw material type, nano-lignocellulose gel is used to replace nano-bamboo cellulose gel.

[0053] Comparative Examples 2 and 3

[0054] Comparative Example 2 and Example 1 use the same raw material types, but the specific component ratios are different, as shown in Table 2.

[0055] Table 2 Specific raw material ratios for comparative examples 2 and 3

[0056]

[0057] Comparative Example 4

[0058] Comparative Example 4 uses commercially available pure copper electrodes with a purity of 99.99%.

[0059] Performance testing

[0060] In order to further study the influence of each component and preparation parameter on the performance, the present application further carries out the following examples for verification. During the inspection, each example and comparative example is made into an electrode in the same manner as in Example 1, and the electrode is tested.

[0061] Conductivity test

[0062]

[0063]

[0064] The test data of Examples 1-2 and Comparative Example 4 are shown in Table 3.

[0065] Table 3 Test results of conductivity of Examples 1, 2 and Comparative Example 4

[0066]

[0067] Referring to Table 3, the conductivity of Examples 1 and 2 is slightly higher than that of Comparative Example 4. This may be because, first of all, graphene is a two-dimensional material composed of a single layer of carbon atoms, which has extremely high conductivity, and a thin layer of graphene nanosheets has a very large specific surface area, which means that it can form a large number of interface contact points with other materials. When the graphene and the copper base are formed into a good interface with the aid of gel, they may form a continuous conductive network, which helps the transmission of electrons in the entire material, thereby improving the conductivity.

[0068] Secondly, the introduction of nano bamboo cellulose can form a specific oriented structure in the composite material, such as a brick-like mesh structure, which helps to improve the thermal and electrical conductivity of the material. This structure also has good packaging properties, allowing graphene to achieve high-performance directional thermal and electrical conductivity when used in small amounts.

[0069] The conductivity of Example 2 is similar to that of Example 1, but the amount of thin-layer graphene nanosheets added in Example 2 is about twice that of Example 1. This may be because, due to the limited amount of copper powder and nanocellulose gel, the excess graphene is not fixed on the periphery of the copper powder, but is sieved out during the sieving process in the preparation step. Although Example 2 can also obtain a product with good conductivity, it also leads to a waste of cost.

[0070] Mechanical strength test

[0071]

[0072] The test data of Example 1 and Comparative Examples 1-4 are shown in Table 3.

[0073] Table 4 Mechanical strength test results of Example 1 and Comparative Examples 1-4

[0074]

[0075] Referring to Table 4, the data of Example 1 is significantly better than those of Comparative Example 1 and Comparative Example 4, mainly because the nano-wood cellulose gel is used to replace the nano-bamboo cellulose gel in Comparative Example 1. The nano-bamboo cellulose gel has strong hydrogen bonding interactions between highly crystalline nanofibrils and a densely arranged nanostructure, and can withstand large plastic deformation before breaking, which helps to improve the toughness and impact resistance of the material.

[0076] In addition, the introduction of nano-bamboo cellulose can form a specific orientation structure in the composite material, such as a brick-like network structure. With the assistance of nano-bamboo cellulose, the stacking of graphene sheets can be effectively prevented, which is also beneficial to improving the mechanical properties of the material.

[0077] In Comparative Example 2, too little nano bamboo cellulose gel was added, which may result in that most thin-layer graphene nanosheets did not form a tightly bonded interface with the copper base. In Comparative Example 3, too much nano bamboo cellulose gel and too many thin-layer graphene nanosheets were added, but the amount of copper powder was limited, resulting in agglomeration during mixing, and graphene was not evenly distributed on the surface of the copper powder, which affected the performance of the material.

[0078] Wear resistance test

[0079]

[0080] The test data of Example 1 and Comparative Examples 2 and 4 are shown in Table 3.

[0081] Table 5 Wear resistance test results of Example 1 and Comparative Examples 2 and 4

[0082]

[0083] Referring to Table 5, the wear amount of Example 1 and Comparative Example 2 is less than that of Comparative Example 4, which shows the effect of nano bamboo cellulose gel and thin-layer graphene nanosheets. At the same time, the wear resistance of Example 1 is better than that of Comparative Example 2, which illustrates the importance of the specific ratio of copper powder, nano bamboo cellulose gel and thin-layer graphene nanosheets.

[0084] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An electrode material suitable for large current, characterized in that: According to weight percentage, it includes 30-50 parts of micron-grade copper powder, 3-6 parts of nanocellulose gel, and 0.5-1.8 parts of thin-layer graphene nanosheets; and its preparation method includes the following technical steps: 1) mixing micron-sized copper powder and nanocellulose gel to obtain a first mixture; 2) mixing the first mixture with the thin-layer graphene nanosheet to obtain a second mixture; 3) evaporating the water from the second mixture under vacuum conditions for 1-4 hours, and then annealing the mixture at 750-850° C. to obtain a product to be processed; 4) Screening the material to be treated to obtain a copper-based composite material.

2. The electrode material suitable for large current according to claim 1, characterized in that: The nanocellulose gel is nano bamboo cellulose gel.

3. The electrode material suitable for large current according to claim 2, characterized in that: The mass concentration of nanocellulose in the nanocellulose gel is 0.4-0.65%.

4. The electrode material suitable for large current according to claim 1, characterized in that: In step 4), the material to be processed is screened through a 4500-5000 mesh vibrating screen.

5. An application of an electrode material suitable for large current, characterized in that: It comprises an upper electrode and a lower electrode which are bonded together. The upper end of the lower electrode is provided with contact bridges on both sides of the upper electrode. The upper end of the upper electrode is provided with a guide column, and the outer periphery of the guide column is sleeved with a spring.

6. The use of an electrode material suitable for large current according to claim 5, characterized in that: The contact bridge is a multi-layer thin metal sheet structure, and gaps are left between upper and lower adjacent metal sheets.

7. The use of an electrode material suitable for large current according to claim 5, characterized in that: The contact bridge is a multi-layer thin copper sheet structure.